The Impact of Quality Information on the Environmental Accounting Disclosure: A Case study for the Arabian Gulf Oil Company in Libya. - Elgobbi , . Eltayeb M; El-Ghannai , Eltaib E. E (مجلة الدراسات الاقتصادية, 2018)
The aim of this study, which is conducted on the quality of information and its impact on the environmental accounting disclosure, is to explore the prospective key strategies and policies by which quality of information can play an important role for the success of environmental accounting disclosure. This study derives its significance from the importance of the topic and its concept; it concentrates in particular on developing a potential framework for the lead to effective and optimal ideas in order to enhance the performance of the Arabian Gulf Oil Company (AGOC) in Libya with regard to quality of information and its impact on the environmental accounting disclosure. The present study used as questionnaire as a tool for collecting the relevant data and also to achieve the objectives of the study. The study sample consisted of (31) respondents selected randomly from the financial & administrative administration as well as from the environmental safety & security administration in the (AGOC), as both administrations have a direct relation in dealing with the information and its quality as well as dealing with the environmental accounting disclosure. The statistical package for social sciences (SPSS) program was used to analyze and examine the hypotheses, and some statistical methods such as the weighted mean, standard deviation, regression analysis and other appropriate analysis were used in order to discover the effect of quality of information on environmental accounting disclosure in the company. Executing the analysis on the study hypotheses, the study reached a number of results, the most important of which are: there is a significant impact (statistically significant) for the quality of information on the level of details related to environmental accounting disclosure, as well as a statistically significant effect for the quality of information on the nature and types of information related to environmental accounting disclosure.